2014
DOI: 10.1213/ane.0b013e3182a7f73c
|View full text |Cite|
|
Sign up to set email alerts
|

Nitrous Oxide for the Management of Labor Pain

Abstract: The literature addressing nitrous oxide for the management of labor pain includes few studies of good or fair quality. Further research is needed across all of the areas examined: effectiveness, satisfaction, and adverse effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(105 citation statements)
references
References 56 publications
2
96
1
2
Order By: Relevance
“…The use of nitrous oxide may be an ideal adjunct in this situation. 38 However, although common in other countries, nitrous oxide is currently only rarely available in the US for labor analgesia. Various medical staff (e.g., nurses) and nonmedical support personnel (e.g., trained birth attendants such as doulas) may be resources in collaborative efforts to ensure that women in labor receive patient-centered pain management care.…”
Section: Discussionmentioning
confidence: 99%
“…The use of nitrous oxide may be an ideal adjunct in this situation. 38 However, although common in other countries, nitrous oxide is currently only rarely available in the US for labor analgesia. Various medical staff (e.g., nurses) and nonmedical support personnel (e.g., trained birth attendants such as doulas) may be resources in collaborative efforts to ensure that women in labor receive patient-centered pain management care.…”
Section: Discussionmentioning
confidence: 99%
“…8 Most studies have not found adverse outcomes in the babies of mothers using nitrous oxide for labour but the quality of the studies has been poor. APGAR scores are no different between babies born to mothers who used nitrous oxide for labour and those mothers who used other or no pharmacological labour analgesia.…”
Section: Learning Objectivesmentioning
confidence: 99%
“…El óxido nitroso 49 , de inicio rápido (50 seg), se puede usar en cualquier fase del parto 36 . Se elimina rápidamente de los pulmones y no causa depresión neonatal 50,51 .…”
Section: Fármacos Inhalatoriosunclassified